Marketing Strategy in Sharia Business Aligning Values and Innovation - Teguh Jatmiko, Lukas; Garibaldi, Ganjar; Pratiwi Sakti, B. Retno; Rudianto Sinaga, Jansen; Sunarsi, Denok (International Journal of Sharia Business Management, 2024)
Marketing strategy in Islamic business plays a crucial role in integrating Sharia values ​​with innovation to achieve success in a competitive market. This study explores how Islamic businesses can incorporate consistent Islamic principles with Sharia law while adopting innovation to meet the needs and expectations of modern consumers. Through ethical and responsible marketing approaches, Islamic businesses can build strong customer trust and loyalty. This article also discusses the importance of deep understanding of the target market, development of innovative products, and effective marketing communication in implementing successful marketing strategies. Additionally, this research highlights the importance of collaboration among stakeholders to promote competitive advantage and long-term growth in Islamic business. By focusing on Sharia values ​​and innovation, businesses can create unique value propositions that differentiate them from competitors and drive sustainable growth.